Analisis Pengaruh Harga, People, dan Servqual terhadap Kepuasan Pelanggan Jasa Armada Travel Sport di Kota Samarinda - Odja, Melkior Mbotu Odja; Yudhyani, Eka; Reza, Faizal (Universitas Muhammadiyah Pontianak, 2026)
This study examines shifting preferences toward executive travel services due to the efficiency of the Balikpapan–Samarinda toll road, which has intensified competition. It analyzes the effects of Price, People, and Servqual on Travel Sport customer satisfaction in Samarinda. Using a quantitative causal-associative approach, data were collected through questionnaires from 41 purposively selected respondents and analyzed using multiple linear regression in SPSS. The results show that Price, People, and Servqual have positive and significant partial and simultaneous effects, with Price as the dominant determinant. Management should maintain competitive pricing, staff competence, and fleet reliability. Keywords: Customer Satisfaction; Loyalty; People; Price; Servqual